2020
DOI: 10.3892/ijmm.2020.4819
|View full text |Cite
|
Sign up to set email alerts
|

ROS‑mediated hypomethylation of PRDX5 promotes STAT3 binding and activates the Nrf2 signaling pathway in NSCLC

Abstract: Deoxyribonucleic acid (DNA) epigenetic modification has been linked to specific sequences of CpG islands and plays roles in the progression of lung cancer. In this study, it was found that peroxiredoxin-5 ( PRDX5 ) was highly expressed in non-small cell lung cancer (NSCLC) tissues; however, its specific regulatory mechanisms and functions in NSCLC remain unknown. The present study therefore explored the regulatory mechanism of PRDX5 under conditions of oxidative st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
(38 reference statements)
0
7
0
Order By: Relevance
“…We have previously identified NFE2L2 as a prognostic biomarker of NSCLC 28–33 . As NFE2L1 is a paralog of NFE2L2, it may be similarly related to NSCLC patient outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously identified NFE2L2 as a prognostic biomarker of NSCLC 28–33 . As NFE2L1 is a paralog of NFE2L2, it may be similarly related to NSCLC patient outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, its expression in erythroid progenitors has contributed further to the preliminary rationale for its biomarker potential (34). However, there is still a signi cant gap due to lack of comprehensive erythroid-speci c characterization and broader validation of PRDX5.…”
Section: Resultsmentioning
confidence: 99%
“…PRDX5 is the only atypical 2-Cys PRDXs, mainly located in mitochondrion. PRDX5 is elevated and drives tumorigenic phenotype in colon cancer ( 35 ), non-small cell lung cancer ( 36 ), and gastric cancer ( 37 ). In our study, we also found that PRDX5 could act as an oncogene in HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is reasonable to find that patients with low PRDX1/5 have a more promising response to anti-PD-1 therapy. Furthermore, PRDX5 actives the Nrf2 signaling pathway, which could protect tumor cells from anti-tumor immunity ( 36 , 41 ). Therefore, our results highlight the value of targeting PRDX1/5 to inhibit the progression of HNSCC and turn “cold” tumors into “hot” tumors.…”
Section: Discussionmentioning
confidence: 99%